(untitled) (Oxford, England, 2000)
The Oxford Handbook of Economic Geography is the single most important statement of the scope and status of the vibrant interdisciplinary field of economic geography. It brings together more than 40 leading economists and geographers from around the world. From general statements about the history and evolution of the field to statements about the crucial problems of economic geography, the volume is preoccupied with the rival theories and perspectives that have sustained its recent growth. The volume is also focused upon linkages, including those between the global and the local, between industry location and trade, and between corporate strategy and market structure.
Keywords: Economic geography,Địa lý kinh tế